2012
DOI: 10.1186/1471-244x-12-86
|View full text |Cite
|
Sign up to set email alerts
|

Spatial clusters of suicide in Australia

Abstract: Background Understanding the spatial distribution of suicide can inform the planning, implementation and evaluation of suicide prevention activity. This study explored spatial clusters of suicide in Australia, and investigated likely socio-demographic determinants of these clusters. Methods National suicide and population data at a statistical local area (SLA) level were obtained from the Australian Bureau of Statistics for the period of 1999 to 2003. Standardised morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 43 publications
2
43
1
1
Order By: Relevance
“…Areas with a higher risk of suicide also often have a lower socioeconomic status, along with a higher proportion of indigenous population 14. Our previous study indicated that MTS in QLD and BM in the north of NT showed a much higher suicide risk, proportion of indigenous population and lower socioeconomic status than did the national average, and both were indicated as high-risk clusters using spatial cluster analysis (1999–2003) 14. Suicide by hanging has also increased in indigenous communities, similar to other areas and population groups 38…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas with a higher risk of suicide also often have a lower socioeconomic status, along with a higher proportion of indigenous population 14. Our previous study indicated that MTS in QLD and BM in the north of NT showed a much higher suicide risk, proportion of indigenous population and lower socioeconomic status than did the national average, and both were indicated as high-risk clusters using spatial cluster analysis (1999–2003) 14. Suicide by hanging has also increased in indigenous communities, similar to other areas and population groups 38…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is vital to understand the variations of suicide patterns over time, space, population groups (age, sex and ethnic groups) and the possible reasons for these variations, in order to design effective suicide control and prevention programmes. Previous reports and studies have explored suicide patterns in Australia over time,9–12 methods13 and space 14. From a geographical perspective, the Australian Bureau of Statistics (ABS) suicide reports covered a long period (1921–2010) presented at the state and capital city level 9–11.…”
Section: Introductionmentioning
confidence: 99%
“…We then used these values for the spatial cluster detection. A circular shape was chosen as the shape of the spatial scan window because this is typically used to detect suicide clusters [8, 9]. This circular window was gradually moved on each centroid point of geographical locations, with each circle reflecting a possible cluster.…”
Section: Methodsmentioning
confidence: 99%
“…Qi and colleagues examined spatial suicide clusters in Australia during the period 1999 and 2003 [8]. They found 13 clusters, which included 12 clusters in males and one cluster in females.…”
Section: Introductionmentioning
confidence: 99%
“…It considered both individual and neighbourhood factors associated with the odds of a railway suicide occurring in a cluster. We used a specific spatial parameter size based on the maximum incidence rate rather than using the default value (50%) usually used in the previous studies 15 41. This seems to provide a more precise detection of clusters (cross-checked by visualising local railway suicide rates).…”
Section: Discussionmentioning
confidence: 99%